Pengaruh Pelayanan Fasilitas, dan Harga Terhadap Keputusan Konsumen pada Wuling Perdana Kediri - Dimas Ade Nugroho; Yogi Yunanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aim to know the service influence, facility, and price to consumer decision at Wuling Perdana Kediri. This Research use the quantitative research method because its research data in the form of number and analyzed to use the statistic and also have fulfilled the erudite method that is concrete, objective, measured, rational, and systematic. Population in this research is all consumer of Wuling Perdana Kediri in 1 mean month; moon as much 500 people. While sample that is as much 100 consumer/responder. Method of Intake sample used is No probability Sampling. Method of data collecting passing observation, interview, questionnaire and book or literature. Method analyzes the data use the validity test and test the reliabilities, analyze the doubled linear regress, and test the determinacy (R2). From this research result inferential that: (1) there are influence which significant from service variable by partial to variable of consumer decision. This matter is relied on result sig < 0, 05 and sig. 0, 000 < 0, 05. (2) There are influence which significant from facility variable by partial to variable of consumer decision. This matter is relied on result of test t whereabouts sig < 0, 05 that is sig. 0, 02 < 0, 05. (3) There are influences which significant from price variable by partial to variable of consumer decision. This matter is relied on result of test t whereabouts sig < 0, 05 that is 2, 447 > 0, 068 and sig. 0, 031 < 0, 05. (4) There are influences which significant from service variable, facility, and price by simulate to variable of consumer decision. This matter is relied on by result of Test F that is and sig. 0, 002 < 0, 05 (Ho refused).